(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article presents the results of the study of specific features of retail networks and ways of taking into account these features in the formation of a comprehensive model of management of product transportation in the network. The proposed comprehensive model takes into account such features of the retail network as multiproduct situation, indistinguishability of suppliers and consumers, availability of transit points, cost of storage at the transit point, capacity of warehouses and their load, transportation time and shelf life, priority of outlets and types of products, restrictions on capacity of transport. The proposed model allows solving multiproduct transport problems for trading networks of varying complexity, enabling decision makers to change the complexity of the model.